A case report of uveitis with ocular hypertension - N. V. Konovalova; V. V. Savko; N. I. Khramenko; O. V. Guzun; S. B. Slobodianyk; Iu. A. Zhuravok; V. V. Savko (Ukrainian Society of Ophthalmologists, 2020)
Based on a clinical case, we analyzed the characteristics of diagnosis, course, and treatment of uveitis in the presence of ocular hypertension.